Early-Life Access to a Basic Health Care Program and Adult Outcomes in Indonesia - Ahsan, Md Nazmul; Banerjee, Rakesh; Maharaj, Riddhi (World Bank, Washington, DC, 2020)
Access to primary care during early life can have substantial benefits in developing countries. This study evaluates the long-run impact of the Village Midwife Program in Indonesia. It utilizes the roll-out-variation of the program and link individual background and community characteristics in early childhood to adult outcomes in the Indonesian Family Life Survey. It finds that the presence of a midwife in a community in utero leads to an improvement in overall health, cognition, and economic outcomes among men, but not for women. Greater receipt of antenatal care and skilled birth-attendance could, in part, drive these results.